A Study of Learner Characteristics, School Environment, Achievement and Placement of Scheduled Caste Students of Madhya Pradesh - Pillai, Anil Kumar MB (INDIAN EDUCATIONAL REVIEW, 2014)
The Constitution of India has provided special provision for the upliftment of Scheduled Castes. To impart quality education with all facilities in the same premises Government of Madhya Pradesh started Residential Schools exclusively for Scheduled Caste students at seven divisions. The aim of the programme is to provide nutritious food, rich library, infrastructural facilities and provide an environment which is more conductive to learning. In the present study learner characteristics, school environment, achievement and placement of Scheduled Caste Students have been studied. It was found that these schools have medium level of learning environment. Learners of these schools mostly belonged to the lower strata of the society, thus the scheme of residential schools is helping the poor scheduled caste students in getting quality education. Present study clearly revealed that good percentages of students are joining higher studies after completion of their 12th standard. Thus these schools should be continued and strengthened. Academic achievement of the learners of these schools also revealed that remedial teaching or extra coaching should be introduced in these schools for students who are poor in Physics, Chemistry, Mathematics and English subjects.